Evaluation of α-Amylase Inhibitory, Antioxidant and Cytotoxic Activities of Mimusops elengi Seeds (Bangladesh Pharmaceutical Journal, 2022)
Mimusops elengi Linn., locally known as “Bakul, is a commonly used medicinal plant in Bangladesh to treat several maladities. The purpose of this study was to investigate the antioxidant, α-amylase inhibitory and cytotoxic activity of four different solvent fractions such as petroleum ether, chloroform, ethyl acetate, and water of M. elengi seed. In this study, the high ferric reducing (1.74 ± 0.005) and DPPH free radical scavenging activity (IC50 39.49 ± 0.05 μg/ml) was observed in the ethyl acetate fraction. The highest amount of flavonoid content (1059.80 ± 2.15 mg of CE/g) and total antioxidant capacity (0.17 ± 0.005) was present in chloroform fraction. On the other hand, the ethyl acetate fraction exhibited the highest total phenolic content (182.90 ± 0.38 mg of GAE/g). Crude methanolic extract showed highest inhibition of α-amylase with IC50 value of 4.09 ± 0.08 mg/ml. The brine shrimp lethality bioassay of ethyl acetate fraction exhibited maximum toxicity with low LD50 value 127.10 μg/ml. Thus, extracts of M. elengi seed could be a source of antioxidant, cytotoxic and α-amylase inhibitory activity containing compounds.Bangladesh Pharmaceutical Journal 25(1): 16-25, 2022 (January)